Análise dos resíduos sólidos de desarenador do tratamento preliminar de esgotos sanitários da cidade de Maringá - PR - Tomiello, Erick Christian (2008)
Several are the wastes generated in a wastewater treatment plant, they could vary since biological muds, until solid materials kept in the system of preliminary treatment. Basically the system of preliminary treatment, used in wastewater treatment plants, involves the retreat of raw materials presents in the sewerage and the retention of solid particles composed of mineral debris, seeds, peels of eggs, pieces of bones, hair and other, that they are denominated usually of grit. Those operations have fundamental importance to the good operation of the treatment station, in the measure in that they condition the flow for the subsequent units of treatment. The amount and quality of those wastes are of difficult characterization once they are function, mainly, of the sanitary education of the population served by sewerage. The objective of this work was to characterize quantitatively and qualitatively those materials in wastewater treatment plants of the city of Maringá - PR, and to analyze the efficiency of the stabilization of the same by an alkaline process, with the intention of proposing a suitable final destination. The found results indicated that the wastes of the screening don't have favorable characteristics, that it can possible they reuse and that the wastes of the grit removal, in raw state, they are classified as coarse sand according to NBR 7.211 (ABNT, 1983) and, in raw state and with the incorporation of burned lime, as waste solid Type IIA - No inert, according to NBR 10.004 (ABNT, 2004a). As the wastes of the grit removal didn't have their elements immobilized by the addition of burned lime, the suitable final destination for the same ones, jointly with the wastes of the screening, it is the disposition in an exclusive landfill of wastes, preferentially built in own ETE.